PERCEIVED BENEFITS OF TRIBAL SUB PLAN (TSP) PROJECT ON TRIBAL BENEFICIARIES IN SELECTED DISTRICTS OF TAMIL NADU - P. Kumaravel; J. John Kirubaharan; D. Thirunavukkarasu (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The study was conducted to assess the perceived impact of the Tribal Sub Plan project on the tribal beneficiaries in terms of socio-economic upliftment. Critical inputs namely sheep/goats, desi chicken, concentrate feed for sheep/goats, dewormers and vaccines, wire net for poultry housing, poultry feed and veterinary first aid kit were provided to the selected beneficiaries. With regard to the perceived direct impact, majority of the beneficiaries opined that their income had increased substantially due to the involvement in the tribal project. Enhanced income was observed through direct marketing and each farmer beneficiary was earning Rs.700-1000/ month by way of selling sheep/goat kids and desi chicken eggs. Among the indirect consequences, significant social, economic and behavioural impact was perceived by majority of the beneficiaries. With regard to social impact, there was increased outside contact followed by changes in food habit, increased organizational participation, better relation and credibility with officers and veterinarians and recognition in the society. With regard to economic impact, majority of the farmers perceived that there was substantial increase in family employment and in addition, few farmers were able to renovate their houses, purchased new land and household materials, invested in monthly savings and cleared their debts. As far as the behavioural impact, majority developed positive attitude towards livestock farming activities and there was increased awareness on the tribal schemes implemented by the Government. Further, majority of the beneficiaries have acquired newer skills namely azolla cultivation, vermicomposting, poultry chick candling and hatching due to their active involvement in the tribal project.